Um estudo de recifragem por proxy para controle de acesso em diferentes aplicações - Barbosa, Alyson Ricardo de Araújo (Universidade Federal Rural do Semi-Árido, 2018)
With the ever-increasing data flow on the computer network, there is a need to find a way to deliver data safely and free from intrusion. Nonetheless, that should be achieved without losing access control to authorized users. One method that can be used in this context is encryption. And, within cryptography, proxy re-encryption appears as a promising approach to this problem. In this paper, we will cover different recent uses of proxy re-encryption registered in articles in the IEEE Xplore database.
Monografia
Keywords: Controle de acesso; Recifragem por proxy; Criptografia; Access control; Proxy re-encryption; Encryption; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::SISTEMAS DE INFORMACAO